Optical Coherence Tomography Angiography Compared With Optical Coherence Tomography for Detection of Early Glaucoma With High Myopia - Chang, Pei-Yao; Wang, Jiun-Yi; Wang, Jia-Kang; Huang, Tzu-Lun; Hsu, Yung-Ray (Frontiers in Medicine, 2022)
Purpose: To investigate the diagnostic abilities of the perfusion density(PD) and structural thickness parameters in the peripapillary and macular regions measured by optical coherence tomography angiography(OCTA) and optical coherence tomography(OCT) and to test if their diagnostic abilities of early glaucoma are different between highly myopic(HM) and nonhighly myopic(NHM) patients. Methods: A total of 75 glaucoma patients and 65 controls were included in the analyses. The glaucoma detection abilities of macular PD and peripapillary PD, along with macular ganglion cell-inner plexiform layer(mGCIPL) thickness and peripapillary retinal nerve fiber layer(pRNFL) thicknesses were compared between the HM and NHM group. Diagnostic ability was assessed by area under the receiver operating characteristics (AUC) curves, adjusted by age, axial length, and signal strength. Results: The diagnostic ability of macular PD and mGCIPL thickness had no significant difference in both HM or NHM group. However, the diagnostic ability of peripapillary PD except in temporal section was significantly lower in the HM group than in the NHM group (all p<0.05). The diagnostic ability of the superior, nasal, and average pRNFL thickness was also significantly lower in the HM group than in the NHM group. (all p<0.05) Conclusion: This study demonstrated that although peripapillary PD and macular PD were both significantly reduced in patients with highly myopia, the diagnostic ability of peripapillary PD in HM patients was significantly lower than that in NHM patients, while macular PD was not. Macular OCTA along with OCT imaging should be included in the imaging algorithm in early glaucoma diagnosis in highly myopic patients.